Development of Leveled Reading Books Based on the ADDIE Model to Improve Elementary Students’ Reading Comprehension - Sapariah Sapariah; Muh. Fahrurrozi; Baiq Rismarini Nursaly (Sumber Belajar Sejahtera, 2026)
This study aims to develop and evaluate the effectiveness of leveled reading books based on the ADDIE model to improve reading skills and text comprehension among elementary school students. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants included 45 fifth-grade students, consisting of 10 students in the small-group trial and 35 students in the large-group trial. Data were collected through pretest-posttest assessments, expert validation sheets, and questionnaires. Quantitative data were analyzed using the normalized gain (N-Gain) formula, while qualitative data were analyzed descriptively. The results indicate that the developed product is valid and effective. The small-group trial showed an N-Gain score of 0.69 (moderate category), while the large-group trials demonstrated high effectiveness with N-Gain scores ranging from 0.79 to 0.80. In addition, student and teacher responses were categorized as excellent, indicating high acceptance and practicality of the product.In conclusion, leveled reading books developed through the ADDIE model are effective instructional materials for enhancing students’ reading comprehension and literacy engagement. This study contributes to the development of differentiated literacy instruction in elementary education.